Evaluating Training Program Using Physiological and Biochemical, and Physical Indicators On National Artistic Gymnastics League For Men - Jawad Kadhim, Mohammed; Salman Ahmed, Wesam (Journal of Physical Education, 2016)
The aim of the research is to identify some physiological and biochemical indicatorsvalues as well as physical abilities of national artistic gymnastics league for men. In additionto that, the researcher aimed at designing scientific bases for evaluating training programs ofgymnastics coaches according to some physiological, biochemical indicators and physicalabilities for the national artistic gymnastics league for men. The researchers hypothesized nodifferences in some physiological, biochemical and physical abilities between pre andposttests. The researchers used the experimental method; the subjects were national artisticgymnastics league for men. High and low blood pressure, and blood sugar of the subject were collected and treated using proper statistical methods. The researchers concludedimprovement in high and low pressure after special preparation period on three apparatuses;horizontal bar, parallel bars and pommel horse. They also concluded that blood sugarconsumption increased gradually after effort and recovery during special preparation periodfor all three apparatuses.